A Novel Approach of Stability Awareness Routing in MANETs - Grover, Lovedeep; Kaur, Maninder; Verma, Lal Pratap (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
In this paper, we introduce a novel approach of stabilityawareness routing for efficient utilization of Bandwidth by useof Bandwidth Threshold. Earlier work on routing in MANETshad resulted in several routing protocols which targets at findinga viable route from source to destination without taking intoconsideration battery backup or Bandwidth availability for datatransfer & they frequently fails to discover stable routesbetween source and destination, resulting in networkoverloading & discarding of data packets. In Novel stabilityawareness routing protocol, selects only the route which canprovides minimum required Bandwidth and uptime to supportthe data transfer for the expected duration. The Novel stabilityawareness routing (NSAR) resolves the problem of SADSRprotocol & provide better results in terms of route discoverysuccess rate with multiple route establishment, maintenanceoverheads and enhancing QOS.